Analytical performance of a loop-mediated isothermal amplification assay for leishmania DNA detection in sandflies and direct smears of patients with cutaneous leishmaniasis (2018)
Loop-mediated isothermal amplification (LAMP) is ideal for the detection of Leishmania DNA as it is a quick and easy-to-perform test that does not require complex or sophisticated equipment or infrastructure. However, the application of this technique in the detection of Leishmania DNA has not been comprehensively analyzed to date (analytical validation). Our objective was to evaluate the sensitivity and analytical specificity (anticipated reportable range [ARR], the limit of detection [LoD], and accuracy) of LAMP targeting the 18S rRNA gene in the diagnosis of six New World Leishmania species. We then applied the validated LAMP assay across 50 samples of sandflies and 50 direct smears from a recent outbreak of cutaneous leishmaniasis in Colombia to determine its diagnostic performance. The LAMP assay exclusively amplified the DNA of Leishmania spp., and an ARR of between 1 × 10 4 and 1 × 10 -2 equivalent parasites/mL was determined. An LoD of 1 × 10 -2 equivalent parasites/mL was established and there was no statistically significant variation in terms of accuracy. Finally, a sensitivity of 100% in direct smears and sandflies samples was calculated and a specificity of 90.9% for direct smears using microscopy as reference and 96.8% for sandflies using real-time polymerase chain reaction as reference were determined. To our knowledge, this is the first attempt to analytically validate a LAMP test to detect Leishmania DNA, which showed good diagnostic potential from sandflies and direct smear samples. Copyright © 2018 by The American Society of Tropical Medicine and Hygiene.